Electronic Toll Collection System based on Radio Frequency Identification System - Raed Abdulla; Aden Abdillahi; Maythem K. Abbas (Institute of Advanced Engineering and Science, 2018)
This papaer entitled electronic toll collection system based on Radio Frequncy Identification System explained in detail based on current issue at toll collection system. There are some obstacles faced every day where the users spent their valuable time in queue at tollgate due to traffic congestion as well as using traditional manual method in most existing toll ETC system to collect toll from road users. Besides that, the barrier design where each vehicle stop waiting until barrier lift which consider source of time delay. To tackle stated problems, an electronic toll collection system is proposed which based on RFID technology. The integrated system consists of two main sections, electronic sides where all input data received from while database management office is where all necessary information stored. To compare the current ETC system, in this research elaborated internet of things where all data transmit through cloud and then to the main office in real time. Not only that, there is some enhancement based on barrier design where, gate is remained open for all vehicles with sufficient tags without requiring to stop to eliminate time delay.By check system throughput compare to existing toll systems, various tests have been carried out in different method where proposed system throughput much higher percentage the current system.